2017
DOI: 10.21276/aimdr.2017.3.6.og3
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Rupture: A Two-Year Review at a Teaching Institution

Abstract: Background: To determine the socio-demographic and obstetric causes of uterine rupture, the case fatality rate and association of these factors with maternal mortality among patients of uterine rupture. Methods: A retrospective study between January 2010 to December 2011. Result: During the study period, 18637 deliveries were conducted and 69 cases of uterine rupture were admitted giving the incidence of 0.37% of deliveries. Of the 69 women 53.5% had spontaneous uterine rupture. Among these the most frequent f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
1
Order By: Relevance
“…19 In present study, hypovolemic shock was present in 15 (32.60%) which is higher than that of Ghadei R and Team which observed shock in 4.3% of study subjects. In our study we had not find a single case of vasico vaginal fistula but a study from Yemen reported a 3.3% incidence of VVF.…”
Section: Resultscontrasting
confidence: 64%
“…19 In present study, hypovolemic shock was present in 15 (32.60%) which is higher than that of Ghadei R and Team which observed shock in 4.3% of study subjects. In our study we had not find a single case of vasico vaginal fistula but a study from Yemen reported a 3.3% incidence of VVF.…”
Section: Resultscontrasting
confidence: 64%